Phylogenetic systematics and integrative taxonomy contribute to weed biological control - Marvaldi, Adriana (2024)
Taxonomy and systematics are at the base of any biological research, providing the scientific names and evolutionary context to access the biological information needed. The biological control of weeds (BCW), like many other fields, often suffers from the “taxonomic impediment” generated by incomplete taxonomic knowledge or lack of available taxonomic experts on the particular taxa involved (i.e., weed plants and their potential biocontrol agents). Further, most groups with described species require revision by specialists using modern taxonomic methods. Systematists in the different taxonomic groups have the knowledge and experience to perform the accurate identification of the species involved in the study, to recognize if they are non-native species, or if they are new to science. Their expertise is crucial for identifying the organisms involved in BCW, including hybrids or cryptic species. The practice of phylogenetic systematics allows the discovery of evolutionary relationships and natural taxa that are valuable in making host range predictions. This contribution emphasizes the crucial role played by phylogenetic systematics and integrative taxonomy in weed biological control.